Conformable fixture systems with flexure pins for improved workpiece damping. (February 2020) - Craig, Oliver; Picavea, Javier; Gameros, Andres; Axinte, Dragos; Lowth, Stewart
Graphical abstract: Highlights: A novel fixture concept based on tuneable flexure support structures is demonstrated. Analytical models are used to define key dimensions of the flexure geometry. Finite element models are used to simulate whole fixture systems for additive manufacture. Flexures accommodate workpiece geometric variability to reduce clamping deformation. Frequency tuning of flexures enables damping of workpiece vibration in end milling. Abstract: Holding low stiffness freeform components during machining is challenging, due to clamping deformation and vibration issues. This paper presents a novel fixture concept that conforms to the surfaces of freeform components by filling the space between locators with arrays of deformable flexure pins. The introduction of flexures has minimal effect on workpiece-fixture dynamic response, meaning no changes to the tooling or machining parameters of an existing process are necessary. The flexure concept is shown to reduce clamping forces for a freeform component compared to a conventional fixture, while simultaneously reducing workpiece deformation. A mathematical model is used to define the flexure dimensions required to achieve the desired dynamic response, and a Finite Element (FE) model is used to predict workpiece-fixture clamping interactions, showing good agreement with experimental values for workpiece deformation. A flexure-based fixture is evaluated in a milling experiment, and found to reduce workpiece vibration when machining excitation causes flexures to resonate. Models reliably predict the relative machining responses of conventional and flexure-based fixtures, and allow observation of flexure resonant behaviour. The concept was shown to reduce the clamping force required to hold a workpiece by up to 60 % (with deformation reduced by up to 47 % for a given clamp force), and reduce workpiece vibration in milling by 30 % compared to a conventional fixture.